RST-IoT - uma ferramenta de apoio a especificação de requisitos de sistemas de software IoT - Albuquerque Júnior, Ednilson da Silva (Brasil, 2020)
The Internet of Things (IoT) is the result of the constant evolution in which technology is found, and can be understood as a new technological paradigm that brings together the physical and virtual worlds with the objective of providing software systems everywhere through everyday objects. However, at the same time that technology evolves, knowledge and greater control over it must be taken into account, especially in this new area, where the application domain is not easy to understand. Research on its hardware and applications continues to advance, however, there is little effort in the area of ​​Software Engineering, specifically in Requirements Engineering. Since the specification of requirements for IoT-based software requires different solutions than traditional Requirements Engineering, this work proposes the RST-IoT tool (The Requirements Specification Tool for IoT-based Systems), which aims to assist software engineers in specification of requirements for these systems. RST-IoT was developed specifically to automate the process of specifying requirements for IoT software systems, where it uses a simple design and a few steps to facilitate the process. A methodology based on experimentation was adopted, aiming to develop and validate the tool. This dissertation describes the creation of the RST-IoT, through a feasibility study and an observation study, with the objective of providing assistance to students and software engineers new to the specification of IoT software system requirements.